Knowledge of Partograph Recording and Interpretation and Its Documentation Status in Samdrup Jongkhar District, Bhutan - ., Kuenzang; Pokhrel, Hari Prasad; Dorji, Kezang; Rinzin, Dorji (International Journal of Innovative Research in Medical Science, 2018)
Background: The study aimed to assess the knowledge of partograph recording and interpretation, partograph utilization and documentation status in the district. Methods: A retrospective study of compiled partographs during the last five years (2013-2017) was conducted to assess the documentation status. This was followed by an intervention study conducted using a self-administered questionnaire. Pretest was conducted to obtain the baseline scores. An intervention in the form educational session on partograph recording and interpretation was conducted which was followed by administration of post-test to obtain the end-line scores. The mean differences in the knowledge scores were compared using paired sample T-test. Results: Over one-third (37.5%) of the participants reported lack of refresher courses as the key challenge in use of partographs and only 9.6% of the partographs were found to be complete. Majority (80.4%) of them had a poor level of knowledge during the pre-test, which reduced to 7.1% after the intervention. Paired sample T-test detected significant difference in the mean knowledge scores between the pretest and the post test. Conclusion: Only 54% of the total deliveries were monitored using a partograph and over 90% of these partographs were incomplete. Majority of the participants had a poor level of knowledge during the pre-test.